DESIGN AND DEVELOPMENT OF AN AUTOMATED SMART BROODER SYSTEM FOR MINI POULTRY FARMS - Alisher Khamroev, (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract.  Early-stage  chick  rearing  requires  controlled  environmental conditions to ensure survival, growth, and disease prevention. Manual brooder systems used  in  small  poultry  farms  often  suffer  from  temperature  instability,  improper ventilation, and inefficient feeding management. This paper presents the design and implementation of an automated smart brooder system intended for mini poultry farms. The  proposed  system  integrates  environmental  sensors,  microcontroller-based automation, heating regulation, ventilation control, lighting scheduling, and feeding alerts.  Experimental  evaluation  demonstrates  improved  thermal  stability,  reduced chick mortality, and decreased human intervention. The developed solution provides a low-cost and scalable approach suitable for rural and small-scale poultry production.